Fixed point results for β − F−weak contraction mappings in complete S-metric spaces - Khomdram, Bulbul; Rohen, Yumnam; Khan, Mohammad Saeed; Fabiano, Nicola (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: This paper introduces the concept of β − F-weak contraction by using the concepts of F−weak contraction and α − ψ−contraction.Methods: The use of the β − F-weak contraction proves some fixed points theorems in the framework of S−metric spaces.Results: The obtained results on fixed points in S−metric spaces generalize some known results in the literature.Conclusions: The β − F−weak contraction generalizes some important contraction types and examines the existence of a fixed point in S−metric spaces. The results are used to solve a non-linear Fredholm integral equation.
Keywords: fixed point; S-metric space; β − F−weak contraction; nonlinear integral equatin